Sensors, Medical Images and Signal Processing: Ubiquitous Personalized Health Monitoring - Müller, H.; Foncubierta-Rodriguez, A.; Depeursinge, A.; Section Editors for the IMIA Year-book Section on Sensor, Signal, and Imaging Informatics (Yearbook of Medical Informatics, 2012)
To summarize excellent research in the field of medical sensor, signal and imaging informatics published in the year 2011.Synopsis of the articles selected for the IMIA (International Medical Informatics Association) Yearbook 2012 through a manual initial selection and a peer review process to find the best paper in this domain published in 2011.Current research in the field of sensors, signal, and imaging informatics is characterized by theoretically sound techniques and evaluations with focus in imaging informatics. An increased number of systems with embedded signal processing where sensors include signal processing were observed in 2011. In all domains, pragmatic solutions with the goal of clinical impact have grown, including in developing countries where simple, robust techniques are combined to address primary and simple medical problems with potentially high impact. Finally, recent advances in image and signal processing are moving towards patient-based modeling.The best paper selection of articles on sensors, signal, and imaging informatics shows examples of excellent research on methods concerning theoretically sound original development in this field in the year 2012.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; image processing; signal processing; medical sensors